Vibronic spectra of protonated hydroxypyridines: contributions of prefulvenic and planar structures. Issue 12 (9th March 2017) - Garcia, R. Lozada; Nieuwjaer, N.; Desfrançois, C.; Lecomte, F.; Leite, S. D.; Manil, B.; Broquier, M.; Grégoire, G.
Abstract : The UV photofragmentation spectra of cold protonated hydroxypyridines display well resolved vibrational structures, interpreted with calculations at the CC2 level. Abstract : Various hydroxypyridine derivatives are endogenous or synthetic photosensitizers which could contribute to solar radiation damage. The study of their excited states could lead to a better understanding of their action mechanisms. We present here the ultraviolet (UV) spectra of the protonated 2-, 3- and 4-hydroxypyridine. These spectra were obtained with an experimental device coupling an electrospray ion source with a cold quadrupole ion trap and a time of flight mass spectrometer. They display well resolved vibrational structures, with a clear influence of the position of the OH group. These results are interpreted with excited states calculations at the coupled cluster CC2 level.